Permian stromatolites associated with bivalve coquina beds-Angatuba, SP, Brazil (Teresina Formation, Parana Basin) - Sallun Filho, William; Ghilardi, Renato Pirani [UNESP]; Silva e Silva, Loreine Hermida; Hachiro, Jorge (Coquina Press, 2012)
Silicified stromatolites have been described in the Permian Teresina Formation, Passa Dois Group, of the Parana Basin. These stromatolites occur as blocks in the Fazenda Monte Alegre area at the headwaters of the creek known as Corrego Catanduva in the municipality of Angatuba. These blocks originate from the Serra de Angatuba region and were recognized in a road that was cut in the midst of sandstones and siltites. The stromatolites are isolated bioherms that are domed to subspherical with a flat base in profile and a rounded to lenticular shape in plan view. The stromatolites exhibit a reddish coloration and are composed of microcrystalline quartz. Lamination is continuous, non-columnar, and anastomosed, showing parallel to divergent growth; however, divergent columns also occur, especially at the tops of the bioherms. The lamination is fine and well preserved, with alternating light and dark laminas. Microfossils of filamentous cyanobacteria are preserved and were related to the genera Microcoleus and Rivularia. Silicified bivalves occur in association with the stromatolites and are preserved in the form of coquina beds and rare isolated specimens within the bioherms. The described specimens belong to the Pinzonella illusa biozone, with representatives of the species Pinzonella illusa, Angatubia cowperesioides, and Houldausiella elongata. The formation environment of these stromatolites is associated with tidal plains of shallow, brackish, relatively calm, warm waters of good luminosity with the presence of weak currents. There was likely a low level of predation, and the environment may have been hypersaline. The coquina beds associated with the stromatolites indicate a probable proximal tempestite, i.e., they were formed near the coastline. The stromatolites were originally composed of carbonates, although these were replaced by silica during early diagenesis.
Keywords: Stromatolite; Coquina bed; Permian; Parana Basin; Teresina Formation; Brazil